Urinary Prognostic Biomarkers in Patients With Focal Segmental Glomerulosclerosis - Kalantari, Shiva (Kowsar, 2014)
BACKGROUND: Focal segmental glomerulosclerosis (FSGS) is a type of nephrotic syndrome which is diagnosed by renal biopsy. Degree of the proteinuria, renal dysfunction, histologic findings and the response to therapy are some factors used for evaluating the prognosis of FSGS. OBJECTIVES: In the present study, we attempted to discover some protein candidates for disease prognosis related to glomerular filtration rate (renal dysfunction). PATIENTS AND METHODS: Urine samples were collected from ten patients. Urine proteome was extracted and trypsinated. Digested peptides were separated and identified by nano-flow LC-MS/MS. Protein content were determined using label-free quantification method. Protein profiles were analyzed using supervised multivariate statistical method. RESULTS: Output of a predictive model was 54 significant proteins of which ribonuclease 2 and haptoglobin had the greatest fold change in terms of overrepresentation and underrepresentation in patients with the best and worse prognosis, respectively. Complement and coagulation cascades were the only significant pathways which were impaired in FSGS. CONCLUSIONS: Urinary biomarkers can potentially be used as non-invasive prognostic markers. However these candidate biomarkers need further validation by an alternative method and in a larger cohort.